PENGARUH VARIASI PRODUK DAN BRAND AWARENESS TERHADAP MINAT BELI (STUDI KASUS DI MY ROTI) - Euis Winarti; Dadang Surya Kencana; Ade Rani (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to analyze how product variation and brand awareness affect purchasing interest at My Roti Cikarang, or at PT. Yamazaki Indonesia. The company has innovated by offering a variety of bread products, but data shows that there is instability in production planning, delays or cessation of production due to lack of interest in the product has an impact on customer satisfaction and potential loss of revenue, and low brand visibility is an obstacle to purchasing interest. This type of research is quantitative by taking primary data through observation, questionnaires, and interviews, and secondary data through data provided by the company, sample items and production items with time series data, namely 2022-2023. The sampling technique is with field observation and documentation studies. The analysis model used is a multiple linear regression model. Based on the results of the analysis and hypothesis testing, product variation has a positive effect on purchasing interest in the My Roti brand of 0.070 or 7%, but product variation does not have a significant effect, because the t-count value is 0.842 <t table 1.996 and sig. 0.403> α 0.05. Brand awareness has a positive influence on the purchase interest of the My Roti brand by 0.932 or 93.2%, and its influence is significant, because the t-value is 12,810> t-table 1,996 and sig. 0.001 <α 0.05. Product variation and brand awareness have a positive influence on the purchase interest of the My Roti brand by 330,754 and the influence given is significant on purchase interest. Because the F-value is 330,754> F-table 3.13 and sig. 0.001 <α 0.05.